Hyperuricemia in Patients with Chronic Renal Failure: A Single Center Study, Pakistan - Najam Ud Din Mufti, Raza Muhammad Khan, Abdul Haseeb, Waqas Sardar, Saad Hanan, Sajjad Ali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: a level of serum uric acid more than or equal to 70 mg/l (420 mol/l) in males and 60 mg/l (360 mol/l) in women is considered hyperuricemia. It has been established in many studies to be a risk factor or a factor in the progression of chronic renal disease. Recent experimental and epidemiological studies link hyperuricemia to chronic kidney disease (ckd), arterial hypertension, and cardiovascular disease, raising the issue of whether medicines are effective in the prevention of renal illness. The goal of this study is to discover whether there is a relationship between chronic renal disease and hyperuricemia. Methodology: From january 1st to december 1st, 2015, this single-center study was done at the department of nephrology at marcy teaching hospital in peshawar, pakistan (12 months). We included all chronic renal disease patients with associated hyperuricemia who were admitted to a hemodialysis unit. Results: A total of 72 individuals were included in the study. The prevalence of hyperuricemia was 15.20 percent. The average age of the patients was 35.5 years. The age group of 40 to 60 years old accounted for 54.6 percent of the total. Patients with hypertension accounted for 49% of the total, with diabetes and hypertension being linked in 11% of the cases. In 42.3 percent of patients, renal insufficiency was moderate. In more than 90% of the patients, hyperuricemia was found. Hyperuricemia was statistically linked to profession, age, hematuria, proteinuria, and hypertension. In 85 percent of patients, allopurinol was prescribed as a treatment. More than 12% of patients had an unsatisfactory course of treatment. Conclusion: Several recent investigations have shown the role of hyperuricemia in chronic renal disease. To determine its true influence on the prevention and treatment of chronic renal disease, randomised study on large sizes must be conducted.